A health integrated platform for pharmacy clinical intervention data management and intelligent visual analytics and reporting - Jennifer Frestel; Stephanie Wai Khuan Teoh; Claire Broderick; Anna Dao; Monica Sajogo (Elsevier, 2023)
Objective: Our initiative aimed to improve the system used to capture pharmacist clinical interventions to better support staff to document, manage and identify trends in medication-related problems (MRPs). The aim of the study was to develop an electronic tool which is easily accessible by most electronic devices with secure data storage and access. Methods: A REDCap® database was designed for documentation of pharmacy clinical interventions. Information documented can be retrieved in real-time and can be integrated to Microsoft Power BI® for real-time data visualisation. The dashboards were customised to display useful information including pharmacy clinical intervention details, common MRPs, common medications involved available to users at real time. Results: A total of 4343 interventions were documented from July 2022 to March 2023. The most common MRPs were omission of regular medications 876 (20.17%), condition untreated 722(16.62%), and contraindications apparent 451 (10.38%). The most common medications involved include iron 244 (5.62%), enoxaparin 231 (5.32%), macrogol laxatives 208 (4.79%), multivitamin 206 (4.74%), colecalciferol 179(4.12%), tramadol 156 (3.59%). Conclusion: This study demonstrated the significance of integration of health application tools of REDcap and Power BI in the data management and intelligent visual analytics and reporting.